The Effect of Good Corporate Governance, Corporate Social Responsibility, and Environmental Performance on Financial Performance in State-Owned Enterprises Listed on the Indonesia Stock Exchange in the 2019-2022 Period - I Kadek Doni Wira Prasetya; Komang Adi Kurniawan Saputra; Ida Ayu Surasmi (PT Keberlanjutan Strategis Indonesia, 2026)
Study This aiming For analyze Influence Good Corporate Governance, Corporate Social Responsibility, and Environmental Performance On Financial Performance of State-Owned Enterprises Listed on the Indonesia Stock Exchange for the 2019-2022 Period . Research This due to fluctuations performance state-owned enterprise finances and difference results study previously related connection third factor the to performance finance . Research This use method quantitative with approach analysis panel data regression . Population in study This consists of of the 34 state-owned companies which then selected with technique purposive sampling , obtained 18 companies that met the requirements criteria research . The data used originate from report annual and reports sustainability company during period 2019-2022. The main theory used in study This is Institutional Theory. The results of the study show that Good Corporate Governance influential positive to performance finance . Corporate Social Responsibility influential positive to performance finance . While that , Environmental Performance influential negative to performance finance .